Transforming livestock production systems in East Africa through scaling novel forages: The grass 2 cash @scale journey - Sibiko, Kenneth Waluse; Mwema, Emmanuel; Hansen, Andreas; Mwendia, Solomon W; Burkart, Stefan; Notenbaert, An (2024)
The seminar presentation shares information about a fascinating project implemented in Kenya, Uganda and Ethiopia between 2021-2024. It provides information about the design, implementation and major achievements, as well as key research findings from the project. Our experiences from the Grass 2 cash @Scale project will be useful for other researchers to better design future projects. It also offers an opportunity to disseminate our research findings and attract feedback from the research community for further improvement.